Novel Approaches for Interpretation of the THMC Behaviors of Unfrozen and Frozen Unsaturated Soils - Li, Yao (Université d'Ottawa / University of Ottawa, 2023)
The soils in arid and semi-arid regions are typically in an unsaturated state. Three phases; namely solids (i.e., soil), liquid (i.e., water) and pore-air (i.e., gas) commonly exist in unsaturated soils. Soil mechanics for unsaturated soils are widely used towards understanding the hydro-mechanical behavior of unsaturated soils. The major focus of these studies during the past three decades is directed towards interpreting and predicting the flow, shear strength and volume change behaviors of unsaturated soils using the saturated soil properties and the soil water characteristic curve (SWCC) as a tool. However, for rigorous understanding, the coupled influence of thermo-hydromechanical-chemo (THMC) behavior of unsaturated soils is required. Such studies would be valuable for interpreting the influence of climate changes on the fundamental behavior of both frozen and unfrozen soils. To achieve this goal, the focus of this PhD thesis has been directed towards investigating the THMC behaviors of unsaturated soils with emphasis on water retention behaviors for unsaturated unfrozen and frozen soils. A multi-modal or bimodal SWCC can be used as an effective tool for developing a fundamental understanding and predicting the behavior of unsaturated soils considering the influence of macro and microstructure. Such an approach will be valuable for all soils, including unimodal SWCC which is a special case of bimodal SWCC. For addressing this objective, a hypothesis is introduced to link the soil pore size distribution (PoSD) curve to the bimodal SWCC. The relationships between the soil PoSD curve and the bimodal SWCC equations are discussed extending the proposed hypothesis using two equations: namely, the rigid equation and the simplified equation for the two well-known traditional unimodal SWCC equations from the literature. The calibration processes built for both the equations performance was evaluated for various types of soils. The results suggest that both the modified equations provide excellent comparison with the measured data. The rigid equations provide comprehensive information about the macropores and the micropores of the bimodal SWCC; however, the simplified equations facilitate a flexible yet simple curve-fitting process. The relationships between the proposed equations and the available methods for the bimodal SWCC from the literature are also discussed. In addition, a technique is developed based on regression analysis to estimate the key features for bimodal SWCCs. Novel models are derived from the pore-size distribution (PoSD) curve of the SWCC to predict the SWCCs for coarse- and fine-grained soils and linked to the well-known SWCC fitting equations from literature. Three simple methods are proposed for predicting the scanning SWCCs of coarse-grained soils, extending this philosophy. A modified SWCC model is built based on the theoretical background developed for the PoSD curve that can predict the SWCC of fine-grained soils taking account influence of the initial water content and stress state. In addition, a coupled SWCC model is proposed as a part of this study for explaining the influence of multiple soil parameters. To model soil freezing characteristics curve (SFCC) of unsaturated frozen soils, SFCC models with well-defined model parameters are developed extending thermodynamics principles and are linked to well-known SWCC models from the literature. Various zones in the SFCC are discussed along with providing rational explanation for the hysteretic effects using the proposed models. In addition, comparisons are provided between the measured and the predicted results using the proposed models successfully highlighting the effects of salinity and the initial water content on the frozen unsaturated soils. Finally, the proposed generalized THMC framework is successfully used to explain the complex behaviors of unsaturated soils. The developed models are promising and can be used as valuable tools for numerical modeling of the THMC behaviors of unsaturated soils in all environments.